Genetic polymorphisms of PRKAA1 (AMPKα1) and postherpetic pain susceptibility: Multicenter, randomized control, and haplotype analysis study - Mei, Yang; Chen, Qi; Li, Yu-Ping; Chen, Yao-hua; Xia, Juan; Zeng, Jie; Yu, Le-hua; Li, Wei; Cui, Jian (Frontiers in Molecular Neuroscience, 2023)
Adenosine 5’-monophosphate (AMP)-activated protein kinase (AMPK) is a pivotal regulatory protein in energy metabolism. In a pilot study, we found that AMPK-associated energy metabolism imbalance in neurons contributes to the occurrence and maintenance of neuropathic pain (NeP). This study aimed to explore the relationship between genetic polymorphisms of AMPK gene (Rs13361707, rs3792822, and rs10074991) in PRKAA1 and postherpetic neuralgia (PHN) in Chinese individuals. 132 patients with PHN and 118 control individuals were enrolled in this study. All blood samples were shuffled and blinded to the person performing the haplotype analysis. Rs13361707, rs3792822, and rs10074991 PRKAA1 genotypes were identified in all participants. Dominant and recessive models were used for evaluating the association between these nucleotide polymorphisms and PHN susceptibility. A haplotype analysis of PHN patients and healthy controls was performed.Clinical characteristics between the two groups were not significantly different (P > 0.05) except that the ages in control subjects were younger than the PHN patients (P < 0.05). Genotypes and allele frequencies are significantly different between the PHN patients and control subjects for the rs13361707 and rs10074991 polymorphisms (P < 0.05), but not for rs3792822 (P > 0.05). In addition, the CCG haplotype of rs13361707-rs3792822-rs10074991 correlated negatively with PHN occurrence, but TCA was positively correlated with PHN. (P<0.05). Our results indicate that PRKAA1 gene polymorphisms rs13361707 and rs10074991 were associated with a risk of PHN, and that the CCG haplotype of rs13361707-rs3792822-rs10074991 correlated negatively with PHN occurrence in haplotype analysis. TCA was positively associated with PHN in Chinese individuals.